THE EFFECT OF FIBROTOLS ON THE PROPERTIES OF FINE-GRAINED CONCRETE - PhD, dotsent Raximov Shavkat Turdimurotovich; Tayanch doktorant Xudoynazarova Qunduz Djumanazarovna; Tayanch doktorant Obidjonov Jaxongir Toxir o‘g‘li; Assistant Nusratov Jonibek Xikmatulla o’g’li (Web of Journals Publishing, 2024)
The article presents the level of research, composition and properties of fiber-based concrete. The main direction for improving the properties of concrete is the use of fiber fibers as an additive to concrete.
Keywords: cement, fiberglass, fiber-reinforced concrete, composition, properties, basalt fibers, strength, durability